1999
DOI: 10.1046/j.1471-4159.1999.721574.x
|View full text |Cite
|
Sign up to set email alerts
|

A Nuclear Microscopic Study of Elemental Changes in the Rat Hippocampus After Kainate‐Induced Neuronal Injury

Abstract: Abstract:The effect of intracerebroventricular kainate injection on the elemental composition of the hippocampus was studied in adult Wistar rats, at 1 day and 1, 2, 3, and 4 weeks postinjection, using a nuclear microscope. An increase in calcium concentration was observed on the injected side from 1 day postinjection. The increase peaked at 3 weeks postinjection, reaching a concentration of 18 times normal. Large numbers of glial cells but no neurons were observed in the lesioned CA fields at this time, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…These mechanisms not only include inhibition of mitochondrial function and increases in intracellular calcium ion, due to depolarization, but also free radical generation ). Our nuclear microscopic studies have clearly indicated a steady increase in calcium ion at 1, 2, and 3 weeks after KA injection (Ong et al, 1999). This increase in calcium ion may be responsible for the stimulation of many calcium-dependent enzymes including isoforms of PLA 2 (Sandhya et al, 1998), calpain II (Ong et al, 1997), and endonucleases during KA-induced neurotoxicity.…”
Section: Phospholipase a 2 Activity In Kainic Acidinduced Neural Cmentioning
confidence: 54%
“…These mechanisms not only include inhibition of mitochondrial function and increases in intracellular calcium ion, due to depolarization, but also free radical generation ). Our nuclear microscopic studies have clearly indicated a steady increase in calcium ion at 1, 2, and 3 weeks after KA injection (Ong et al, 1999). This increase in calcium ion may be responsible for the stimulation of many calcium-dependent enzymes including isoforms of PLA 2 (Sandhya et al, 1998), calpain II (Ong et al, 1997), and endonucleases during KA-induced neurotoxicity.…”
Section: Phospholipase a 2 Activity In Kainic Acidinduced Neural Cmentioning
confidence: 54%
“…Iron may promote the formation of free radicals by A␤, via the methionine 35 residue of A␤ [240]. A late increase in iron level is detected in the degenerating hippocampus after KA induced excitotoxicity, using the quantitative method of nuclear microscopy [241]. In addition, there is a shift in the oxidation state of iron, with more cells becoming positive for ferrous iron at a later time (months).…”
Section: Possible Links Between Ad Associated Iron Changes and Slow Ementioning
confidence: 99%
“…The validity of μ-PIXE for quantitative measurement of Ca concentration/maps has been shown previously in animal models in which excitotoxicity is a fundamental process, such as brain ischaemia, where time-dependent increases in key brain structures are seen [38]. Likewise, in the kainic acid model of epilepsy, site-specific Ca ion increases were seen in key epileptogenic brain regions during the asymptomatic phase of the disease up to 4 weeks after disease initiation [39]. On the basis of our μ-PIXE results, it would appear that the 7-day time-point would still be a valid time-point for assessing the effects of therapeutic interventions in neuroinflammation, increasing the utility of this model.…”
Section: Discussionmentioning
confidence: 63%